Structure and thermal property of intumescent char produced by flame‐retardant high‐impact polystyrene/expandable graphite/microencapsulated red phosphorus composite. (26th August 2019) - Liu, Jichun; Li, Hang; Chang, Haibo; He, Yunpeng; Xu, Airong; Pan, Bingli
Summary: This paper is aimed to illustrate the structure and thermal property of intumescent char produced by flame‐retardant polymers containing expandable graphite (EG). For this purpose, high‐impact polystyrene (HIPS) flame retarded by EG individually or in combination with microencapsulated red phosphorus (MRP) was prepared. The results indicate that the intumescent char from HIPS/EG/MRP composite, which contains a small amount of phosphorus element and more oxygen element, is much more compact and continuous than that from HIPS/EG composite with identical loading of flame retardant due to binding effect of phosphoric acid and its derivatives. The intumescent char produced by HIPS/EG/MRP composite exhibits much enhanced thermal and thermo‐oxidative stability as well as thermal‐insulating effect, which can withstand destruction of heat and oxygen effectively and thus provide a good fire‐proof barrier. The temperature beneath this intumescent char is decreased significantly in case of action by flame. By comparison, the porous and loose intumescent char generated by HIPS/EG composite has poor thermo‐oxidative endurance, and most of it can be consumed in air at high temperature without effective protection for the polymer. This has resulted in remarkable increase in flame retardancy of the HIPS/EG/MRP composite.